KONSTRUKSI MAKNA KEGIATAN “TRAVELING & TEACHING” KOMUNITAS 1000 GURU OLEH RELAWAN - Allegra Gabriella Esther; Hanny Hafiar; Heru Riyanto Budiana (Jurnal Nomosleca, 2018)
This study builds on the phenomena occured in Traveling and Teaching activity by 1000 Guru Community, whose concern is about the education in the remote and isolated areas in Indonesia. In said activity, volunteers will have to pay some amount of money to bring them to one of the remote areas in Indonesia for 2-3 days of stay, where they will spend those days teaching the kids who are in need of help. In this study, will be found the ways of how the volunteers interpret their Traveling and Teaching activity. This study has the approach of constructivist paradigm methodology, with the use of phenomenology and Phenomenology Theory. The purpose of this study is to present the data found during months of researches. The interpretation of this movement is as an activity, as an activity to show their concerns towards education, as an understanding behind how the education works at remote and isolated areas, and also the meaning of Traveling and Teaching that helps those volunteers to interpret this movement better.